Rare case of Stevens-Johnson syndrome with bronchiolitis obliterans as a chronic complication. Issue 4 (25th April 2022) - Mitani, Kazuki; Hida, Shinya; Fujino, Hisanori; Sumimoto, Shinichi
Abstract : A young girl in her teens presented with fever, rashes and various mucocutaneous symptoms. Flat erythematous macules were seen mainly on the limbs, without blisters or skin detachments. The lips were swollen with crusts and haemorrhage. The oral cavity and pharynx showed ulcerative lesions with exudate. Severe bilateral ocular lesions with pseudomembrane formation and corneal epithelial defects were present. Also, urogenital lesion and gastrointestinal symptoms with frequent haematochezia were observed. Her symptoms and pathological findings were consistent with Stevens-Johnson syndrome. She was treated with prednisolone and methylprednisolone pulse therapy. Her ocular and cutaneous symptoms improved without severe chronic complications. However, 1 month later, she developed dyspnoea, and a pulmonary function test revealed severe obstructive ventilation disorder. After discharge, she was regularly followed up for respiratory complications. High-resolution chest CT performed 9 months after onset revealed mosaic perfusions and bronchiectasis, consistent with bronchiolitis obliterans.